Analysis of Customer Behaviour using Modern Data Mining Techniques - Nasti, SJ; Asgar, M; Butt, MA (International Journal of Computer Sciences and Engineering, 2025)
As we know enormous amount of data is present on the Internet and in order to get value out of this data and present the information to the user in a very simple form, researchers are working hard to collate this data.This colossal size of data on Internet is the most important source for decision making and marketing now-a-days. The paper presents a proposed model to understand online customer’s buying behaviour based on decision tree and artificial neural network models.Our model is comparatively good at predicting the precision of customer’s buying behaviour.